2014
DOI: 10.3109/10428194.2013.855307
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the apoptosis pathway in hematologic malignancies

Abstract: Apoptosis is a cell death program that is well-orchestrated for normal tissue homeostasis and for removal of damaged, old, or infected cells. It is regulated by intrinsic and extrinsic pathways. The intrinsic pathway responds to signals such as ultraviolet radiation or DNA damage and activates “executioner” caspases through a mitochondria-dependent pathway. The extrinsic pathway is activated by death signals induced, for example, by an infection that activates the immune system or receptor-mediated pathways. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
158
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(163 citation statements)
references
References 165 publications
(180 reference statements)
4
158
0
1
Order By: Relevance
“…Dysregulation of the apoptotic pathways may not only promote tumorigenesis, but also render the cancer cells resistant to treatment. Therefore, it's very important to control cellular apoptosis strictly for the organisms, especially hematopoietic system as it has a high turnover rate [36]. In this study, we found celastrol could cause apoptosis of APL cells both in vitro and in vivo , indicating celastrol has anti-leukemia effect through inducing apoptosis.…”
Section: Discussionmentioning
confidence: 62%
“…Dysregulation of the apoptotic pathways may not only promote tumorigenesis, but also render the cancer cells resistant to treatment. Therefore, it's very important to control cellular apoptosis strictly for the organisms, especially hematopoietic system as it has a high turnover rate [36]. In this study, we found celastrol could cause apoptosis of APL cells both in vitro and in vivo , indicating celastrol has anti-leukemia effect through inducing apoptosis.…”
Section: Discussionmentioning
confidence: 62%
“…DISC activates caspase 8, which then activates downstream caspases to initiate apoptotic cell death [19,73]. In the intrinsic pathway stress signals including DNA damage and loss of survival factors lead to the permeabilization of the OMM, which leads to loss of membrane potential and release of apoptogenic proteins such as cytochrome c from the IMS.…”
Section: Introductionmentioning
confidence: 99%
“…4). In addition of mitochondria-mediated apoptosis pathway, membrane death receptor-mediated apoptosis and endoplasmic reticulum stress-mediated apoptosis are other important signaling pathway of apoptosis [53]. Further investigations that revealed whether compound 12P also activate other signaling pathway of apoptosis are under performed.…”
Section: Discussionmentioning
confidence: 99%